Microencapsulation of citronella oil for solar-activated controlled release as an insect repellent - Ribeiro, António David Martins (2016)
This study investigates the functionalization of titanium dioxide nanoparticles on the surface of polymeric microcapsules as a mean to control the release of encapsulated citronella through solar radiation. This allows for the release of a mosquito repellent without human intervention, as the sunlight works as a release activator. The TiO2 nanoparticles were synthetized using a modified sol–gel and hydrothermal method, with a crystallite size of the order of 10 nm and a specific surface area >250 m2/g. Transmission electron microscopy observations enabled the confirmation of the mesoporous structure. The nitrogen doping effect and changes in pH (pH = 3, 6 and 9) of the precursor solution was studied from photocatalytic and photoluminescence experiments. Polyurethane microcapsules were prepared using a modified interfacial polymerization method. The surface topography ofthe microcapsules was observed with scanning electron microscopy, while the release efficiency was quantified using gas chromatography coupled with mass spectroscopy. In-vitro bioassays using live mosquitoes further attested the controlled release repellence effect of these photocatalytic microcapsules by inhibition of these vectors. The results showed that functionalizing the microcapsules with nanoparticles on their surface and then exposing them to ultraviolet radiation effectively increased the output of citronella into the air, repelling the mosquitoes